General aspects of the inflammatory reaction in COVID-19 - Calil , Leonardo Borghetti; Joviliano, Renata Dellalibera (Seven Editora, 2023)
COVID-19 has become a challenge in recent times in different scenarios including areas of health, economy, and education, among others. In the years 2020 and 2021, the world experienced a pandemic caused by the SARS-CoV-2 virus that causes the disease. Since then, understanding the etiopathogenic mechanisms of the new coronavirus has become a challenge. Thus, it becomes the objective to present the role of TCD4+ and TCD8+ lymphocytes in COVID-19, studying the mechanism of action of these cells, their activation, effects on the body, and immunomodulation. A bibliographic review was carried out on the PubMed platform, using literature published between the years 2020 to 2023, and the keywords: COVID-19, T lymphocytes, inflammation, SARS-COV 2, and cytokines. Analyzing published data, we found that after virus infection, CD4+ T lymphocytes are induced to release pro-inflammatory cytokines, such as INF-gamma, which activate cytotoxic CD8+ T lymphocytes, which, as the name implies, cause cell toxicity that ends in lysis of infected cells and destruction of the machinery used by the virus to reproduce. Lysis is brought about by proteins, such as perforins, which induce the appearance of pores on the surfaces of cell membranes. Although the inflammatory response is important for fighting the virus, it can occur in an exacerbated way, releasing a harmful amount of the inflammatory cytokine IL-6 and this overexpression is responsible for decreasing the efficiency of TH 1 cells, TCD8+ lymphocytes, and immunoglobulins. In short, it is important to understand how knowledge of the immunopathogenic of COVID-19 can be fundamental to learning more about the disease itself and to pave the way for its resolution. Thus, the chances of death from the disease decrease, as professionals are aware of its effects and can indicate more accurate treatments for its resolution. DOI:https://doi.org/10.56238/emerrelcovid19-013